2005
DOI: 10.1097/00008483-200507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Maximal Graded Exercise Test on Glutathione as a Marker of Acute Oxidative Stress

Abstract: The current results indicated that in sedentary individuals, a maximal treadmill GXT is an effective technique for inducing acute oxidative stress as evidenced by GSH system responses, with full return to resting baseline levels within 60 minutes of recovery. The potential for using this model in assessing oxidative stress responses to cardiac and pulmonary rehabilitation is of clinical interest, with a need for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 11 publications
4
39
0
3
Order By: Relevance
“…The authors suggested that the low-intensity exercise may fall below the threshold needed for improvement while the improvement in highintensity exercise may have been abolished by free radicals generated at high intensities [34]. Although the TAC remained unchanged following the intervention in the exercise group compared with the control group, this would not necessarily reflect the acute increase in oxidative stress associated with a single exercise bout [35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the low-intensity exercise may fall below the threshold needed for improvement while the improvement in highintensity exercise may have been abolished by free radicals generated at high intensities [34]. Although the TAC remained unchanged following the intervention in the exercise group compared with the control group, this would not necessarily reflect the acute increase in oxidative stress associated with a single exercise bout [35].…”
Section: Discussionmentioning
confidence: 99%
“…When free radical formation is not excessive, the body is able to maintain the resting intracellular levels of GSH and GSSG by reducing GSSG back to GSH [15]. Under strenuous exercise conditions there is an increase in free radical production causing GSSG creation, which exceeds GSH supply and uptake [16][17][18][19]. The GSH:GSSG ratio, which reflects this imbalance, has become a sensitive biomarker of the reduction-oxidation (redox) status [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The GSH:GSSG ratio, which reflects this imbalance, has become a sensitive biomarker of the reduction-oxidation (redox) status [13,16,17]. Decreases in the GSH:GSSG ratio have been interpreted as a sign of oxidative stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few studies reporting the effects of treadmill exercise on redox state in football players or non-athletes [1,[33][34][35][36][37], the most adequate comparison of our results is with studies performed on young handball players [4,5,31], although the exercise test performed in these studies was cycling ergometer testing. However, because it has been shown that endogenous oestrogen may have a protective role in exercise-induced oxidative stress among female handball players [38] and female non-ath- exercise load and consequently longer duration of the exercise test.…”
Section: Statisticsmentioning
confidence: 99%